Application of augmented reality technologies for education projects preparation - Anna V. Iatsyshyn; Valeriia O. Kovach; Volodymyr O. Lyubchak; Yurii O. Zuban; Andriy G. Piven; Oleksandra M. Sokolyuk; Andrii V. Iatsyshyn; Oleksandr O. Popov; Volodymyr O. Artemchuk; Mariya P. Shyshkina (Academy of Cognitive and Natural Sciences, 2020)
After analysis of scientific literature, we defined that concept of "augmented reality" has following synonyms: "advanced reality", "improved reality", "enriched reality", "mixed reality" and "hybrid reality". Analysis of scientific literature and own practical experience of the use of augmented reality technologies application in educational practices allowed to state next: augmented reality technologies have a great potential for application in education; there are some cases of augmented reality use for school education; positive aspects of augmented reality technologies application in higher education institutions are confirmed by experiments (isolated cases); only few universities in Ukraine apply augmented reality technologies to educate students; only few universities in Ukraine have special subjects or modules in schedule to teach students to develop augmented reality technologies; various scientific events, mass events, competitions are held in Ukraine, and specialized training on the augmentation of augmented reality technologies is carried out, but this is non-systematic and does not have special state orientation and support. Features of introduction of virtual and augmented reality technologies at Sumy State University (Ukraine) are identified: "e-learning ecosystems" was created; in 2019, augmented and virtual reality research laboratory was established. Advantages and disadvantages of project activity in education are described: project activity is one of the most important components of educational process; it promotes creative self-development and self-realization of project implementers and forms various life competencies. It is determined that augmented reality application for implementation of educational projects will help: to increase students' interest for educational material; formation of new competences; increase of students' motivation for independent educational and cognitive activity; activation of educational activities; formation of positive motivation for personal and professional growth; conditions creation for development of personal qualities (creativity, teamwork, etc.). Current trends in implementation of educational projects were identified: most of the winner projects were implemented using augmented reality technology; augmented reality technologies were used in projects to teach different disciplines in higher education institutions. Augmented reality technology application for project activity has positive impact on learning outcomes and competitiveness of the national workforce; it will enhance the country's position in the global economic space.